A Clinical study of Matra Vasti and an ayurvedic indigenous compound drug in the management of Sandhigatavata (Osteoarthritis) - Shah, Mayuri R. (Medknow Publications Pvt Ltd, 2010)
Sandhigatavata is described under vatavyadhi in all ayurvedic classical texts. Osteoarthritis is the most common articular disorder which begins asymptomatically in the second and third decades and is extremely common by age 70. Here Matra Vasti (therapeutic enema) was given with Bala taila as Vasti is the best treatment for vatavyadhies. It has vatashamaka and rasayana properties. Indigenous compound drug containing Guggulu, Shallaki, Yastimadhu, Pippali, Guduchi, Nirgundi, Kupilu and Godanti was given in one group along with Matra Vasti. In this study, 33 patients of Sandhigatavata completed the treatment. Patients were randomly divided into two groups. Sixteen patients in Group-A (sarvanga Abhyanga-swedana + matravasti) and 17 patients in Group-B (sarvanga Abhyanga–swedana+ matravasti + indigenous compound drug). The results of the study indicate that the patients of both the groups obtained highly significant relief in almost all the signs and symptoms of Sandhigatavata.